Acute barium intoxication following ingestion of ceramic glaze. Issue 875 (September 1998) - Thomas, M.; Bowie, D.; Walker, R.
Abstract : A case of deliberate overdose of barium sulphide in a psychiatric setting is presented, with resulting flaccid paralysis, malignant arrhythmia, respiratory arrest and severe hypokalaemia, but ultimately with complete recovery. The degree of paralysis appears to be related directly to serum barium levels. The value of early haemodialysis, particularly with respiratory paralysis and hypokalaemia, is emphasised.